Partial genetic characterization of Stearoyl Coa-Desaturase's structural region in Bubalus bubalis - Lima, A. L.F. [UNESP]; Otaviano, A. R. [UNESP]; Laureano, M. M.M. [UNESP]; Galeazzi, P. M. [UNESP]; de Camargo, G. M.F. [UNESP]; Thomazine, R. B. [UNESP]; Tonhati, H. [UNESP] (Taylor & Francis, 2007)
Conjugated Linoleic Acids (CLAs) comprise a family of positional and geometric isomers of linoleic acid. The main form of CLA, cis-9, trans-11-C18:2 show positive effects in cancer prevention and treatment. The major dietary sources of these fatty acids are derived from ruminant animals, in particular dairy products. In these animals, the endogenous synthesis mainly occurs in mammary gland by the action of enzyme Stearoyl CoA Desaturase (SCD). Different levels of expression and activity of SCD in mammary gland can explain partially the variation of CLA levels in fat milk. Considering a great fat concentration in bubaline milk and the benefit of a high and positive correlation between fat milk and CLA production, this study was carried on with the intention of sequencing and characterizing part of the gene that codifies SCD in buffaloes. Genomic DNA was extracted from blood samples of lactating bubaline which begins to the breed Murrah. After the (acho que nao precisa desse the) extractions, PCR (Polymerase Chain Reaction) reactions were made by using primers Z D1 and E1 F1. The fragments obtained in PCR were cloned into T vectors and transformed in competent cells DH10B line. After this, three samples of each fragment were sequenced from 5' and 3' extremities using a BigDye kit in an automatic sequencer. Sequences were edited in a consensus of each fragment and were submitted to BLAST-n / NCBI for similarity comparisions among other species. The sequence obtained with Z D1 primers shows 938 bp enclosing exons 1 and 2 and intron 1. The primers E1 F1 show 70 bp corresponding to exon 3 of bubaline SCD gene. Similarities were obtained between 85% and 97% among bubaline sequences and sequences of SCD gene described in human, mouse, rat, swine, bovine, caprine and ovine species. This study has permitted the identification and partial characterization of SCD codifing region in Bubalus bubalis specie.
Keywords: CLA; Genomic DNA sequence; Milk; PCR